Originale echt falsch. - Deecke, Thomas; Sturtevant; Williams, Emmett (Bremen : Neues Museum Weserburg, 1999)
Beuys, Joseph ; Bidlo, Mike ; Broodthaers, Marcel ; Caramelle, Ernst ; Duchamp, Marcel ; Durham, Jimmie ; Filliou, Robert ; Fleury, Sylvie ; Förg, Gunther ; Haacke, Hans ; Kippenberger, Martin ; Lakner, Laszlo ; Lavier, Bertrand ; Levine, Sherrie ; Majerus, Michel ; Niemann, Peter ; Oppenheim, Meret ; Pettibone, Richard ; Polke, Sigmar ; Richter, Gerhard ; Roth, Dieter ; Sherman, Cindy ; Spoerri, Daniel ; Steinbach, Haim ; Sturtevant ; Trockel, Rosemarie ; Warhol, Andy ; Williams, Emmett
biografie
Originale : echt falsch, Neues Museum Weserburg, Bremen, 25. Juli bis 24. Oktober 1999
Duits
Engels & Duits
boek